Exercise and sports after COVID?19 ? Guidance from a clinical perspective - Halle, M.; Bloch, W.; Niess, A. M.; Predel, H.-G.; Reinsberger, C.; Scharhag, J.; Steinacker, J. M.; Wolfarth, B.; Scherr, J.; Niebauer, J. (Translational Sports Medicine, 2021)
SARS-CoV-2 infection has emerged as not only a pulmonary but potentially multi-organ disease, which may cause long-term structural damage of different organ systems including the lung, heart, vasculature, brain, liver, kidney, or intestine. As a result, the current SARS-CoV-2/COVID-19 pandemic will eventually yield substantially increased numbers of chronically diseased patients worldwide, particularly suffering from pulmonary fibrosis, post-myocarditis, chronic heart failure, or chronic kidney disease. Exercise recommendations for rehabilitation are complex in these patients and should follow current guidelines including standards for pre-exercise medical examinations and individually tailored exercise prescription. It is of utmost importance to start exercise training at an early stage after COVID-19 infection, but at the same time paying attention to the physical barriers to ensure safe return to exercise. For exercise recommendations beyond rehabilitation programs particularly for leisure time and elite athletes, more precise advice is required including assessment of sports eligibility and specific return-to-sports exercise programs. Because of the current uncertainty of long-term course of SARS-CoV-2 infection or COVID disease, long-term follow-up seems to be necessary.